A new species of Martarega White, 1879, with new distributional records of Notonectidae (Hemiptera: Heteroptera: Nepomorpha) from Brazil - Barbosa, Julianna Freires (Zootaxa, 2020)
A new species of the genus Martarega White, 1879 is described based on brachypterous and macropterous specimens, collected in three regions of Brazil [North (State of Pará), Central-West (State of Goiás), and Southeast (State of Minas Gerais)]. The new species, Martarega nessimiani sp. nov., is very similar to M. brasiliensis Truxal, 1949. These species are differentiated by the rounded shape of the patch of thin setae on the male mesotrochanter, and the angular shape of the hemelytral process stripe of the female hemelytra in the new species, whereas M. brasiliensis has the patch of thin setae with an irregular shape and the hemelytral process stripe almost straight. Illustrations of both species are presented. In addition, we give new distributional records of another 11 species of Notonectidae in Brazil: Martarega membranacea White, M. chinai Hynes, M. bentoi Truxal, M. brasiliensis, M. gonostyla Truxal, M. nieseri Moreira Ribeiro & Nessimian, Buenoa amnigenus (White), B. konta Nieser & Pelli, B. salutis Kirkaldy, B. truxali Nieser, and Notonecta pulchra Hungerford. Copyrigth © 2013 Magnolia Press.